Green Deal Challenges for a Sustainable Future of the EU - CIOT, Melania Gabriela (Presa Universitară Clujeană, 2024)
The European Green Deal (EGD), launched with the goal of making Europe the world’s first climate-neutral continent by 2050, has redefined the contours of sustainable development, necessitating bold decisions, innovative policy frameworks, and the commitment of all stakeholders —governments, businesses, and citizens alike. An objective that puts pressure on political leaders from the Member States to find suitable solution for each European policy included in EGD to be implemented at national level. A lot of debates, conferences, groups were initiated, representatives of political decidents (policymaking), civil society, academia, market structures were called in this complex endeavor. Some Member States are on the right paths, trying to find good solutions for implementation and adjustment the EGD, some are still debating on the suitable policies to implement it, other have groups that are contesting it or almost eludate the topic from the public agenda.